What does social inclusion mean to Singaporeans? A qualitative study of the concept of social inclusion. Issue 2 (2nd July 2016) - Chiu, Marcus Y. L.; Lim, Kheng H.; Chan, Kara; Evans, Sherrill; Huxley, Peter J.
Abstract: In recent years, the term 'social inclusion' has more frequently been mentioned in policy initiatives than academic debates in an Asian context that is characterised by fast economic growth, widening poverty gap, ageing populations and prevalent stigma situation for disabled and marginal groups. It may be particularly meaningful to understand what social inclusion means to the people on the ground, in leading societies like Singapore. This paper presents the qualitative findings of seven focus group discussions with a total of 51 participants of different background, including social workers, social work students, users of mental health services, older community dwellers, adults and youth leaders. The concepts are by and large similar to those found in Hong Kong and UK, surrounding access and opportunities to basic dimensions of community living, but there are also several interesting and unique observations with regard to social inclusion.